Menghayati Cinta Kasih dalam Perkawinan Menurut Seruan Apostolik Amoris Laetitia Nomor 120-142 - Blasius Superma Yese; Antonius P Sipahutar; Fidelis Marianto Halawa (STP Dian Mandala Gunungsitoli Nias Keuskupan Sibolga, 2025)
This article is based on concerns about the declining value of love in married life. There are many couples who end their marriage because they do not find the love that strengthens their marriage. There are many cases of marriages being divorced civilly and annulled by the Church. Pope Francis in his Apostolic Exhortation Amoris Laetitia provides a deep reflection on the value of love that is the main bond in married life and which guarantees the longevity of married life. Married life is basically a life partnership between husband and wife. The basis of that partnership is love. Love allows married couples to experience happiness in married life. This article uses a literature review method. The author collects, reads, and understands various relevant sources and compiles them into a scientific article.